(untitled) (Salud, Arte y Cuidado, 2020)
The objective of the study was to determine the benefits of cardiac rehabilitation in patients with coronary ischemic heart disease who attended a consultation in the secondary prevention and exercise testing unit of the Western Central Cardiovascular Association (Ascardio) Barquisimeto, Lara state. The descriptive study with a quantitative approach, of a non-experimental design and a retrospective cross-sectional section. The technique for collecting data corresponds to a documentary observation, by reviewing the 25 medical records of patients who received cardiac rehabilitation for ischemic heart disease, which includes heart rate, blood pressure, weight, body mass index, biochemical profile (cholesterol, glucemia and triglycerides) before, during and after undergoing the cardiac rehabilitation program. The results reflect that there were relevant benefits in terms of the initial figures of the biochemical profile; cholesterol, glycemia and triglycerides with an estimated mean of 144mg / dl, 95mg / dl and 115mg / dl respectively, in addition to a decrease of ± 10kg in weight and an average BMI of 21.69, in terms of blood pressure and heart rate, an improvement was observed in the systolic blood pressure figures while the diastolic had no variability, thus the heart rate values ​​ranged between 80 and 100 beats per minute. It is concluded that cardiac rehabilitation benefits significantly, as it is effective to control the lipid profile, improve weight, BMI and systolic blood pressure, which is why it is necessary to strengthen and use cardiovascular rehabilitation programs in the management of patients with coronary ischemic heart disease.